PENGARUH LITERASI KESEHATAN TERHADAP KESADARAN KESEHATAN MENTAL GENERASI Z DI MASA PANDEMI - Rudianto, Zalfa Nuraeni (Jurnal Pendidikan Kesehatan (e-Journal), 2022)
The study aims to identify the impact between health literacy and mental health levels for the z pandemic generation. The study USES a descriptive, qualitative method of descriptive description or narrating by using a based analysis of the survey. The subject of research is a z generation limited to 15 to 25 years of age through a Google application form with a total of 50 people. Research has shown that health literacy has contributed to the awareness of the mental health of the z generation, one of which is shown by an understanding of the importance of keeping mental health in check with physical health, but some of its negative traits in society and other external factors such as the number of health workers, Anxiety about when the end of both pandemics and misconceptions regarding mental health itself is still a cause for higher levels of mental disorders among the z generation than at the present time of the covid 19 pandemic.